The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/ja984212w
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Deoxynucleic Guanidine (DNG) Oligomers and Melting Point and Circular Dichroism Analysis of Binding Fidelity of Octameric Thymidyl Oligomers with DNA Oligomers

Abstract: A practical solid-phase synthesis of deoxynucleic guanidine (DNG), a positively charged DNA backbone analogue, is reported. The nucleoside coupling step in the solid-phase synthesis of DNG involves the attack of a terminal 3′-amine upon an electronically activated 5′-carbodiimide to create a protected guanidinium internucleoside linkage. The activated carbodiimide is synthesized in situ by the mercury(II) abstraction of sulfur from an unsymmetrically substituted thiourea in which one substituent is an electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…Kinetic studies have also revealed that the rate of triple helix formation between DNG (T 5 ) with short oligodeoxyadenylates, is an order of magnitude faster than the formation of DNA triplexes at similar salt concentrations [146]. Also, investigations with DNG (T 5 and T 8 ), show that T m 's are significantly reduced by base pair mismatches [147,148]. This suggest that sequence specific base pairing is the predominant mode of binding between DNG and nucleic acid targets, although it has still to be established whether or not this is accompanied by any non-specific binding, via salt bridges, between the oppositely charged backbones.…”
Section: Backbones Containing Sulfonyl Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic studies have also revealed that the rate of triple helix formation between DNG (T 5 ) with short oligodeoxyadenylates, is an order of magnitude faster than the formation of DNA triplexes at similar salt concentrations [146]. Also, investigations with DNG (T 5 and T 8 ), show that T m 's are significantly reduced by base pair mismatches [147,148]. This suggest that sequence specific base pairing is the predominant mode of binding between DNG and nucleic acid targets, although it has still to be established whether or not this is accompanied by any non-specific binding, via salt bridges, between the oppositely charged backbones.…”
Section: Backbones Containing Sulfonyl Groupsmentioning
confidence: 99%
“…Such studies appear close at hand with the development of an efficient solid phase synthetic method for the synthesis of DNG (Fig. 18) [148]. The synthesis involves the coupling of a 3´-amino nucleoside 58, immobilised on a polystyrene resin, with a 5´-carbodiimide intermediate which is derived from the thiourea 59, upon treatment with HgCl 2 .…”
Section: Backbones Containing Sulfonyl Groupsmentioning
confidence: 99%
“…From the plethora of modifications reported hitherto, oligonucleotides with the amide linkage 385 (Scheme 62) have shown very promising antisense properties by displaying higher binding affinity and very good resistance towards nucleases [339,340]. Oligomers with positively charged guanidine [341][342][343][344][345][346] linker 386 lead in the development of new antisense therapeutics, since the attractive forces between them and the negatively charged DNA or RNA contribute significantly to the stability of heteroduplex and triplex structures formed between these species. In addition, they are stable to enzymatic hydrolysis due to the lack of a phosphodiester linkage.…”
Section: Iv181 Carbohydrate Like Amidoximes With Possible Biologicmentioning
confidence: 99%
“…[71Ϫ73] Replacing the phosphate backbone with positively charged guanidinium groups [74] increases the binding of these analogs and makes them resistant to nucleases. [76] Bruice and co-workers have reported the synthesis of deoxynucleotide guanidine oligomers (Scheme 6). [76] Bruice and co-workers have reported the synthesis of deoxynucleotide guanidine oligomers (Scheme 6).…”
Section: Oligonucleotide Analogsmentioning
confidence: 99%
“…[75] The positively charged guanidinium might also give rise to cell membrane permeability by electrostatic attraction of the oligonucleoside to the negatively charged phosphate groups on the cell surface. [76] At first, the resin 6A was loaded with protected and modified nucleotide 6B in the presence of HgCl 2 in DMF to create guanidine 6C. [76] At first, the resin 6A was loaded with protected and modified nucleotide 6B in the presence of HgCl 2 in DMF to create guanidine 6C.…”
Section: Oligonucleotide Analogsmentioning
confidence: 99%